Functional monolithic platforms: Chromatographic tools for antibody purification. Issue 6 (6th May 2013) - Barroso, Telma; Hussain, Abid; Roque, Ana C. A.; Aguiar‐Ricardo, Ana
Abstract Polymer monoliths are an efficient platform for antibody purification. The use of monoclonal antibodies (mAbs) and engineered antibody structures as therapeutics has increased exponentially over the past few decades. Several approaches use polymer monoliths to purify large quantities of antibody with defined clinical and performance requirements. Functional monolithic supports have attracted a great deal of attention as they offer practical advantages for antibody purification, such as more rapid analysis, smaller sample volume requirements and the opportunity for a greater target molecule enrichment. This review focuses on the development of synthetic and natural polymer‐based monoliths for antibody purification. The materials and methods employed in monolith production are discussed, highlighting the properties of each system. We also review the structural characterization techniques available using monolithic systems and their performance under different chromatographic approaches to antibody capture and release. Finally, a summary of monolithic platforms developed for antibody separation is presented, as well as expected trends in research to solve current and future challenges in this field. This review comprises a comprehensive analysis of proposed solutions highlighting the remarkable potential of monolithic platforms.